Surface enhancements, hydrophobicity, and gravitational effects on filmwise and dropwise flow condensation heat transfer for steam in mini-channels - Riley, Gennifer Anne (Kansas State University, 2023)
Condensation heat transfer is an important part of thermal management systems, which take advantage of the latent heat of a two-phase working fluid. The main thermal resistance of filmwise condensation is the liquid film near the condensing surface, and reducing the liquid film thickness enhances condensation heat transfer due to the decreased thermal resistance. This dissertation investigates the effects of hemispherical mounds, porous surfaces, and hydrophobicity on forced condensation heat transfer in micro-channels. Also investigated were the impacts that spatial orientation of the three-sided condensation surface (i.e., gravitational effects) on steam flow condensation, where the cooled surfaces were either the lower surface (i.e., gravity pulls liquid towards the condensing surfaces) or upper surface (i.e., gravity pulls liquid away from the condensing surfaces). A total of five copper test coupons were used, all with 1.9-mm hydraulic diameters for the condensing flows A plain, unmodified, flat surface was used as a control against which to compare the other coupons. Two coupons had a porous monolayer made of 100 µm or 200 µm copper particles. An additional two coupons were modified to have 16, 2-mm diameter hemispheres which were either solid copper or made of 200 µm copper particles. After the initial experiments, the plain coupon was coated in Teflon AF to become hydrophobic (i.e., contact angle approximately 110º). Heat transfer coefficients, film visualization, and pressure drop measurements were recorded for each coupon at mass fluxes of 50 kg/m²s and 125 kg/m²s. The plain, both hydrophilic and hydrophobic, and solid mound coupons were tested in both the standard and inverted orientations. Compared to the plain hydrophilic coupon in standard orientation, the solid mound coupon was found to increase the heat transfer coefficients by 13% to 79%, with the greatest increases occurring at low qualities (x < 0.4) or high qualities (x > 0.6). The sintered mound coupon performed similarly to the solid mound coupon, though with generally less enhancement. Flow visualization suggests that the mounds enhanced heat transfer due to the disruption of the condensate film as well as by reducing the thermal resistance of the film. In the monolayer coupons, both saw modest, less than 20%, heat transfer coefficient enhancement in the mass flux of 125 kg/m²s case, while for 50 kg/m²s, both monolayer coupons had points where the heat transfer coefficient was reduced by up to 10%. When the plain and solid mound test sections were inverted (i.e., condensing surface on the top of flowing steam), minimal differences were found in mound heat transfer performance, while the plain coupon reduces heat transfer coefficients by as much as 14%. The most significant enhancements and condensation mechanism changes occurred for the hydrophobic plain coupon. In the standard orientation, heat transfer coefficients were enhanced by up to 656% and in the inverted case, the enhancement increased by up to 987% compared to the hydrophilic coupon. Visualization showed that in the hydrophobic case, dropwise condensation was occurring. However, no condensation was observed on the inverted hydrophobic surface, likely due to the small size of the condensing droplets; a droplet forces analysis is included which supports decreased droplet size for the inverted, hydrophobic case. Heat transfer coefficient enhancements for low quality (x < 0.4) and low mass fluxes (G = 50 kg/m²s) in the inverted hydrophobic plain coupon and in the hydrophilic solid mound coupon are of particular note, as these conditions provide lower heat transfer coefficients in simple condensers.
Keywords: Filmwise; Dropwise; Condensation; Steam; Surface orientation; Surface enhancement